patonlab/GoodVibes: Bug Fixes & Updated References - Guilian Luchini; Robert Paton; Juanvi Alegre-Requena; Jaime Rodríguez-Guerra; Eric Berquist; JingTao Chen; IFunes; Julia Velmiskina; froessler; Heather Mayes; Shree Sowndarya Santhanalakkshmi Vejaykummar; sibo (Zenodo, 2022)
Version 3.2 fixes a bug when parsing ORCA Single-point calculations when MiniPrint formatting is used. References to the "patonlab" GitHub page have been added